Syntheses, Characterization and Biological Activity of Coordination Compounds of Propanedioic Acid and its Mixed Ligand Complexes with N,N'-Dihydroxy-2,3-butanediimine - Aiyelabola, T.O.; Akinkunmi, E.O.; Osungunna, O (Asian Journal of Chemistry, 2021)
The coordination compounds of propanedioic acid with cobalt(II), nickel(II) and copper(II) ions were synthesized using metal:ligand 1:2. In addition to this, mixed ligand complexes using the same metal ions with propanedioic acid as the primary ligand and N,N'-dihydroxy-2,3-butanediimine as the secondary ligand were also synthesized using M:L1:L2 (1:1:1) where L1 = propanedioic acid, L2 = N,N'-dihydroxy-2,3-butanediimine and M = Cu(II), Ni(II) and Cu(II). The synthesized compounds were characterized using FTIR, UV-vis, magnetic susceptibility measurement and percentage metal composition. The ligand and its metal complexes were tested for their cytotoxic and antibacterial activities. Results indicated that a dimeric square planar geometry was assumed by the cobalt(II) and nickel(II) propanedioic acid complexes. Octahedral geometry was proposed for both cobalt(II) and copper(II) mixed ligand complexes. A dinuclear square pyramidal geometry was suggested for the copper(II) propanedioic acid complex and square planar/octahedral geometry for the nickel(II) mixed ligand complex. The copper(II) propanedioic acid complex elicited the best cytotoxic activity. On the other hand, the nickel(II) propanedioic acid complex showed the remarkable antimicrobial activity. The compounds exhibited good antimicrobial activity in most of the cases with the exception of the cobalt(II) propanedioic acid complex. It was concluded that coordination of the ligands to the metal ions lowered the toxicity of the ligands. It was further concluded that the antimicrobial activity of the compounds was partly dependent on the synergism/additive effect of the intrinsic therapeutic properties of the metal ion and the ligands within the coordination sphere of the complexes synthesized. And this is also in part a function of the geometry assumed by the complexes.